2020
DOI: 10.1108/lodj-07-2020-0313
|View full text |Cite
|
Sign up to set email alerts
|

Does emotional intelligence and empowering leadership affect psychological empowerment and work engagement?

Abstract: PurposeThe objective of this study is to investigate the role of emotional intelligence and empowering leadership in enhancing psychological empowerment and work engagement in private hospitals.Design/methodology/approachA total of 500 questionnaires were distributed to staff nurses at five private hospitals in Riyadh, Saudi Arabia, 100 questionnaires to each hospital, with an achieved response rate of 34.8%.FindingsThe results show statistically significant positive relationships between emotional intelligenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 112 publications
4
67
0
5
Order By: Relevance
“…That is, the higher the emotional intelligence possessed by employees, the higher the employee's work engagement. This study results support previous researches on the relationship of emotional intelligence towards work engagement conducted by Alotaibi et al (2020), Liu & Cho (2018), Zhu et al (2015), Tohemer (2020), Toyama & Mauno (2017), and Karimi & Karimi (2016). These previous researches concluded that emotional intelligence has a positive and significant effect on work engagement.…”
Section: Emotional Intelligence Towards Work Engagementsupporting
confidence: 90%
See 1 more Smart Citation
“…That is, the higher the emotional intelligence possessed by employees, the higher the employee's work engagement. This study results support previous researches on the relationship of emotional intelligence towards work engagement conducted by Alotaibi et al (2020), Liu & Cho (2018), Zhu et al (2015), Tohemer (2020), Toyama & Mauno (2017), and Karimi & Karimi (2016). These previous researches concluded that emotional intelligence has a positive and significant effect on work engagement.…”
Section: Emotional Intelligence Towards Work Engagementsupporting
confidence: 90%
“…Employees who have a higher level of emotional intelligence will tend to show a high level of work involvement. It is in line with research by Zhu et al (2015), Alotaibi et al (2020), Liu & Cho (2018), which suggests that there is a significant relationship between emotional intelligence and work interactions.…”
Section: The Effect Of Emotional Intelligence On Work Engagementsupporting
confidence: 90%
“…The results indicate that workers with higher EI have higher job satisfaction, higher organizational commitment, and are less likely to change jobs. Another recent study has found statistically significant positive relationships between EI, empowering leadership, psychological empowerment and work engagement [14]. This finding suggests that EI training of health workers to improve psychological empowerment and work engagement could help their organisations to improve their relationships with patients, provide better care, and reduce staff turnover.…”
Section: Introductionmentioning
confidence: 91%
“…There is a significant relationship between psychological empowerment and work engagement. Alotaibi et al [14] investigated the role of EI and empowering leadership (EL) in improving psychological empowerment and work engagement. They found significant positive relationships between EI, EL, psychological empowerment and work engagement, suggesting that EI is a good predictor of EL and psychological empowerment, while EL supports work engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who belong to relatively high uncertainty–avoidance cultures are less comfortable with ambiguity or uncertainty and therefore display a high preference for precision, predictability and clear guidance (Hofstede et al , 2010). In the workplace, managers are likely to avoid uncertainty by providing stability for their subordinates and establishing more formal, detailed rules (Alotaibi et al , 2020; Andreassi et al , 2014). Employees tend to be less ambitious, more risk-averse and see job insecurity as threatening (Adler, 1993; Hauff et al , 2015).…”
Section: Hypothesis Developmentmentioning
confidence: 99%